1978
DOI: 10.1177/00220345780570020801
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Occlusal Caries by Measuring the Electrical Resistance of the Tooth

Abstract: The tooth resistance measuring instrument was compared to the traditional method of the explorer examination for the detection of occlusal carious lesions. The findings of the instrument were more sensitive as compared to the traditional method when verified by a histological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 4 publications
0
20
0
1
Order By: Relevance
“…In agreement with this finding are the recent results of Van der Laan et al [1986] who demonstrated enhanced mineral loss underneath artificial fissures where probe damage was initiated. Another method for clinically assessing the mineral content of white spot areas may be the measure of electrical conductivity where the chances of explorer damage are eliminated [White et al, 1978].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this finding are the recent results of Van der Laan et al [1986] who demonstrated enhanced mineral loss underneath artificial fissures where probe damage was initiated. Another method for clinically assessing the mineral content of white spot areas may be the measure of electrical conductivity where the chances of explorer damage are eliminated [White et al, 1978].…”
Section: Discussionmentioning
confidence: 99%
“…The more demineralized the tissue, the lower the resistance becomes. Site-specific measurements have been evaluated in a number of in vitro studies [45][46][47][48] and in vivo studies. 49,50 Surface-specific electrical conductance measurements have been investigated under in vitro conditions, 51 which showed moderate sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…less complicated machine, was of Japanese origin and called the Caries Meter L (G-C International Corp. Re search Park, Leuven, Belgium). Both machines showed great potential for occlusal caries detection [White et al, 1978;Sawadaetal.. 1986]. Monitoring the progress or arrest of occlusal lesions was also shown to be possible using the Vanguard [White et al, 1981].…”
mentioning
confidence: 99%